2021
DOI: 10.1007/s10488-021-01136-4
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Intensive Implementation Support on Fidelity for Four Evidence-Based Psychosis Treatments: A Cluster Randomized Trial

Abstract: Purpose Service providers need effective strategies to implement evidence-based practices (EBPs) with high fidelity. This study aimed to evaluate an intensive implementation support strategy to increase fidelity to EBP standards in treatment of patients with psychosis. Methods The study used a cluster randomized design with pairwise assignment of practices within each of 39 Norwegian mental health clinics. Each site chose two of four practices for implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The progressive nature of the FPE model probably explains the gradual increase in scores in the experimental arm. The success rate is good compared to previous studies, which report mean scores of 3.30-4.00 and 39-50% of sites reaching adequate fidelity after 18-24 months of implementation support (Bond et al, 2009a, b;Kealey et al, 2015;Ruud et al, 2021). However, these studies experienced high rates of discontinuation or unsuccessful implementation.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…The progressive nature of the FPE model probably explains the gradual increase in scores in the experimental arm. The success rate is good compared to previous studies, which report mean scores of 3.30-4.00 and 39-50% of sites reaching adequate fidelity after 18-24 months of implementation support (Bond et al, 2009a, b;Kealey et al, 2015;Ruud et al, 2021). However, these studies experienced high rates of discontinuation or unsuccessful implementation.…”
Section: Discussionmentioning
confidence: 58%
“…A qualitative exploration of the implementation process, in terms of barriers and facilitators, has also been published (Hansson et al, 2022). The ISP was based on the seminal work of the National Evidence-Based Practices (NEBP) project (Bond et al, 2009a;McHugo et al, 2007), and on a recent Norwegian RCT (Ruud et al, 2021). We adopted elements such as the constitution of a local implementation team, regular fidelity measurements with tailored feedback and on-site supervision, kick-off sessions, training and supervision Fig.…”
Section: Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each unit was assigned to receive implementation support for one of the two practices they had chosen and not for the other. Earlier investigations from this trial have shown that the implementation support intervention had a signi cant positive impact on the delity scores [21].…”
Section: Sample and Randomizationmentioning
confidence: 74%
“…This could be addressed by future research, for example, cluster randomised controlled trials to formally compare the effectiveness of different implementation strategies linked to specific outcomes, although it would also be helpful to evaluate a theoretically informed approach to selecting a bundle of implementation strategies to fit a particular context, using more robust study designs. Inclusion of a control group in future evaluations of the implementation of TMH is critical: without this we will remain unable to establish causal links between the presence or absence of a strategy to support implementation, or bundle thereof, and success of implementation (38) offers an illustration of a clustered randomised evaluation of different interventions to support the implementation of four evidenced-based psychosis treatments. Within this study, what was randomised was not the clinical therapies, but rather the level of implementation support, which was limited in the control arm (provision of treatment manuals) and substantially enhanced in the intervention arm to include toolkits, training, implementation facilitation, and data-based feedback.…”
Section: Implications For Future Researchmentioning
confidence: 99%